(untitled) (CIPEEX, 2025)
The article examines whether a taxpayer’s filing of a return that acknowledges a tax debt, by itself, constitutes the Treasury’s tax claim (crédito tributário), thereby dispensing with any further constitutive act by the tax authority. It is a doctrinal and case-law analysis that aims to identify the constitutional grounds and limits of this practice in light of substantive due process. The method combines statutory and constitutional analysis, focused review of the Superior Court of Justice’s Súmula 436, and secondary literature, assessing the model’s reasonableness both internally (coherence and suitability of means) and externally (proportionality). The findings indicate that, where the declaration is valid and voluntary and the law so provides—particularly in taxes subject to self-assessment subject to subsequent homologation—the taxpayer’s acknowledgment of liability renders the tax claim immediately enforceable without an additional constitutive assessment, reconciling collection efficiency with taxpayer safeguards. The study further finds that constitution by declaration does not curtail rights to amendment, challenge, or judicial review, which preserve the rationality of substantive due process. It concludes that using the taxpayer’s declaration to constitute the tax claim is constitutionally legitimate and functionally efficient, provided it rests on clear statutory authorization, is applied with reasonableness, and is accompanied by procedural safeguards ensuring review and adversarial challenge in cases of error or defect.